Application of Prone Position for Patient with Corona Virus Disease: An Interventional Program for Nursing Staff - Wissam Qassem Al-Badri, Khalida Mohammed Khudur (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The coronavirus disease (COVID19) epidemics began in Wuhan, China, in December and have since grown into a serious public health challenge for not only China but also countries around the world. Supportive therapy with advanced hypoxemic respiratory failure management has been demonstrated to improve oxygenation in COVID-19 patients, and the prone position has been proven to improve oxygenation in COVID-19 patients Aims of the study: Assessment of nurses' knowledge toward application of prone position for patient with corona virus, and Assessment of an effectiveness of Educational program on nurses' knowledge toward application of prone position for patient with corona virus Methodology: Pre-experimental study design was used with the application of pre and two post-tests approach. The study was carried out in Kut City/Wasit Province, at AL-Zahraa Teaching Hospital. A non-probability "purposive" sample had been consisted of (69) nurses were selected from at AL-Zahraa Teaching Hospital Results: The results indicate that the nurses at the pre-test are fail at all studied items (M ≤1.66) except, the items number (1 and 21) the responses were fair (M=1.67-2.33). While, after the application of intervention program, nurses expressed significant increased knowledge scores (p< 0.05). Conclusion: There were improving in nurses' knowledge and practices after posttest due to intervention program concerning application of prone position..